A multifunctional and recyclable terbium(iii) coordination polymer: displaying highly selective and sensitive detection of Fe3+ and CrVI anions, and picric acid in aqueous media. Issue 32 (23rd July 2018) - Yang, Yang; Song, Xuerui; Xu, Cong; Wang, Yingzhe; Zhang, Guolin; Liu, Weisheng
Abstract : A multifunctional Tb-CP (1 ) as a recyclable luminescent probe to detect Fe 3+ and Cr VI anions, and picric acid in aqueous media. Abstract : A new two-dimensional (2D) terbium(iii ) coordination polymer (1 ) was successfully fabricated by a solvothermal reaction. Luminescence spectra measurements show that1 can selectively and sensitively detect Fe 3+, Cr VI (CrO4 2− /Cr2 O7 2− ), and picric acid (PA) in aqueous solution. The limits of detection (LODs) of1 toward Fe 3+, Cr VI, and PA are calculated to be 50, 100, and 50 nM, which are significantly lower than the U.S. Environmental Protection Agency's (USEPA) proposed concentrations in drinking water. More significantly, 1 can be easily recycled at least 5 times in the detection process of Cr VI (CrO4 2− /Cr2 O7 2− ) and PA through simple processing. For all we know, 1 is the first multifunctional and recyclable Tb-CP, which displays highly selective and sensitive detection of Fe 3+, Cr VI (CrO4 2− /Cr2 O7 2− ), and PA in aqueous media.